Luz, câmera, sertão bravura e fé na cinematografia de Rosemberg Cariry 1986-1996 - Regis, Iza Luciene Mendes (2003)
From the analysis of the three first films of the director pertaining to the state of Ceará Rosemberg Cariry, it was researched here the perception of which image of “sertanejo”* and hinterland is shown in the screen. Condidering the historiography on the subject, we have understood that the studied film bring a dynamic idea of hinterland and “sertanejo” as transforming agent of his space. Despite the intrepretation which considers him atavic and inert, guided for the determination of the environment, the work of this director tries to show that, through the traditions which renew themselves, the “sertanejos” of his plot turn the symbols which label them as Barbarians into shouts of revolt for a worthy survival, placing themselves in social conflit, and not a natural one, according to what was estipulated to be true. Thus, located in their time, the movies of Rosemberg Cariry act out the reality, over all, propagating the art in the process of transformation. * The man who lives in the hinterland.